Alkaloid profiling of herbal drugs using high resolution mass spectrometry. Issue 3 (31st August 2017) - Nardin, Tiziana; Piasentier, Edi; Barnaba, Chiara; Larcher, Roberto
Abstract: Herbal infusions are consumed worldwide thanks to their "natural" beneficial effects, also due to the presence of alkaloids, although these compounds can have poisonous effects. A method combining online solid‐phase purification with high resolution mass spectrometry was used to define the alkaloid profiles of 117 herbs and 7 commercial blends. Forty‐one alkaloids were quantified in reference to analytical standards, while the presence of a further 116 was confirmed based on accurate mass, retention time, and fragmentation profile. The targeted study showed that 52% of herbs and 42% of commercial blends contained at least one alkaloid. Pyrrolizidines were the most commonly present (26% of samples), with concentrations generally ranging from the quantification limit to roughly 100 μg kg −1 . Moreover, a homemade infusion was studied, finding on average 45% and 6% lower extraction for pyrrolizidine and steroidal alkaloids, respectively. Nevertheless, the migration of pyrrolizidines was confirmed. The study confirmed the frequent presence, natural or accidental, of alkaloids in commercial infusion herbs, highlighting the urgent need for routine and accurate controls. Abstract : In this work we screened more than 120 commercial herbal teas, studying 41 targeted and 116 untargeted alkaloids, including acridinones, acridone, benzophenantridines, glycosteroidals, indoles, isoquinolines, piperidines, piridines, protoalkaloids, purines, pyrrolidines, pyrrolizidines, quinolines, quinolizidines, steroidals, terpenoids and tropanes. The study, performed using liquid chromatography coupled with high resolution mass spectrometry, aimed to evaluate alkaloid migration in homemade hot water infusions.